1991
DOI: 10.1073/pnas.88.5.1661
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a tachykinin peptide NK2 receptor transfected into murine fibroblast B82 cells.

Abstract: Membranes isolated from a murine fibroblast B82 cell line (SKLKB82#3) transfected with the bovine stomach cDNA pSKR56S exhibited binding of [His('25I) Considerable physiological and biochemical evidence exists for distinct NK1-, NK2-, and NK3-tachykinin peptide receptors. The preferred endogenous ligand appears to be substance P (SP) for NK1 receptors, neurokinin A (NKA) for NK2 receptors, and neurokinin B for NK3 receptors (1-4). Nakanishi and coworkers have cloned and expressed in Xenopus oocytes three tachy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

1991
1991
2003
2003

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(15 citation statements)
references
References 32 publications
1
14
0
Order By: Relevance
“…For NK2-receptors, certain peptide (e.g. MEN 10,376, Maggi et al, 1991a) and nonpeptide antagonists (SR 48,968;Emonds-Alt et al, 1992; are more potent at human, bovine, guinea-pig and rabbit NK2 receptors than at rat or hamster NK2 receptors, while the cyclic peptide antagonist, L 659,877 (Williams et al, 1988) or the cyclic pseudopeptide MEN 10,573 (Quartara et al, 1992a) present the converse pattern of affinities (Maggi et al, 1990b;Van Giersbergen et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…For NK2-receptors, certain peptide (e.g. MEN 10,376, Maggi et al, 1991a) and nonpeptide antagonists (SR 48,968;Emonds-Alt et al, 1992; are more potent at human, bovine, guinea-pig and rabbit NK2 receptors than at rat or hamster NK2 receptors, while the cyclic peptide antagonist, L 659,877 (Williams et al, 1988) or the cyclic pseudopeptide MEN 10,573 (Quartara et al, 1992a) present the converse pattern of affinities (Maggi et al, 1990b;Van Giersbergen et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…The amino acid sequences of TK antagonists studied are shown in Table 1: spantide is a well known SP antagonist with some selectivity (about 10 times) for NK1 over NK2 receptors (Buck & Shatzer, 1988) Maggi et al, 1990a) in which Arg in position 11 has been replaced by Lys. Both MEN 10,207 and MEN 10,376 are highly selective NK2 receptor antagonists which discriminate between putative NK2 receptor subtypes (Maggi et al, 1990a;Van Giesbergen et al, 1991;Maggi et al, unpublished data). In preliminary experiments we found that MEN 10,207 antagonized the response to capsaicin of the rat isolated bladder but only at concentrations (10-30,UM) at which the peptide produced some agonist effect of its own.…”
Section: Methodsmentioning
confidence: 99%
“…by GR 82,334, a selective NKI receptor antagonist (Hagan et al, 1991). In the past two years, pharmacological evidence has been provided for the heterogeneity of the tachykinin NK2 receptor 1991a;Buck et al, 1990;Van Giersbergen et al, 1991;Patacchini et al, 1991). Two criteria which allow the distinction between NK2 receptor subtypes have emerged: (a) rank order of potency of antagonists and (b) the different agonist/antagonists character of MDL 28,564.…”
Section: Effect Of Antagonists On the Response To Electricalfield Stimentioning
confidence: 99%
“…However, the receptors involved in tachykininergic control of renal pelvis motility have not been fully characterized. Furthermore, recent studies have provided evidence for the heterogeneity of tachykinin NK2 receptors, possibly reflecting the existence of NK2 receptor subtypes 1991a;Buck et al, 1990;Van Giersbergen et al, 1991;Patacchini et al, 1991). The aim of this study was twofold: (a) to assess the type of tachykinin receptors mediating contraction of the guinea-pig isolated renal pelvis and (b) to assess the relative contribution of different tachykinin receptors to the response produced by endogenous tachykinins released during nerve stimulation.…”
Section: Introductionmentioning
confidence: 99%